Loop Electrosurgical Excision Procedure in Cervical Intraepithelial Neoplasia - Maharjan, Rima; Thapa, BK; Chitrakar, Neershobha; Pariyar, Jitendra; Shrestha, Isha; Joshi, AP; Maharjan, P; Neupane, S (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: To evaluate the treatment outcome and acceptance of LEEP in precancerous cervical lesions. Methods: This is a descriptive study performed in Gynecology Department of Civil Service Hospital, from August 2014 - December 2015 in 28 cases that underwent LEEP forCIN. LEEP was performed as day care procedure under intravenous anesthesia and patient was sent home six hours after procedure. Follow up and further treatment was done after final histopathological reports. Results: Highest percentage ofCIN, 32.14% (9) was seen among 30-39 years age with 16 (57.14%) of parity three and more. 17 (60.71%) presented clinic with symptoms (lower abdominal, backpain, pervaginal discharge) while 11 (39.28%) were diagnosed from routine Pap test. Histopathology revealed four (14.28%)CIN1, eight (28.57%)CIN2, 11(39.28%)CIN3, two adenocarcinoma in situ, one of invasive squamous cell carcinoma, chronic cervicitis and atrophic change with no dysplasia. Margins were negative (satisfactory) in 20 (71.42%) and positive in eight (28.57%) with endocervical involvement in two that required second LEEP while one underwent radical hysterectomy for final diagnosis of invasive squamous cell carcinoma. Conclusions: Hysterectomy is a radical procedure for preinvasive cervical lesions that can be treated with simple procedure like LEEP that saves time and financial resources.